Analisis Faktor – Faktor yang Mempengaruhi Penyerapan Tenaga Kerja pada Sektor Industri di Provinsi Jawa Timur Tahun 2019 – 2023 - Dewi Hayu Nafi’ah; Erna Puspita; Puji Astuti (Equivalent : Journal of Economic, Accounting and Management, 2025)
Abstract : The role of the industrial sector is aimed at strengthening the national economic structure and supporting each other between sectors, improving the national economy, absorbing labor to reduce poverty, and empowering communities which are also expected to increase per capita growth. The purpose of this study is to analyze the effect of Gross Regional Domestic Product (GRDP), Human Development Index (HDI), Minimum Wage (UM) on Labor Absorption (PTK). The population in this study is the entire Industrial Sector in East Java Province in 2019 - 2023 which consists of 29 districts and 9 cities. The sampling technique used in this study is saturated sampling which produces the entire Industrial Sector in East Java Province in 2019 - 2023 which consists of 29 districts and 9 cities. The analysis techniques used are classical assumption tests, multiple linear regression tests, and hypothesis tests. The results of the study partially state that Gross Regional Domestic Product (GRDP), Human Development Index (HDI), Minimum Wage (UM) have an effect on Labor Absorption (PTK). The results of the study simultaneously stated that Gross Regional Domestic Product (GRDP), Human Development Index (HDI), Minimum Wage (UM) have an effect on Labor Absorption (PTK). Abstrak : Peranan sektor industri ditujukan untuk memperkokoh struktur ekonomi nasional dan saling mendukung antar sektor, meningkatkan perekonomian nasional, menyerap tenaga kerja guna mereduksi kemiskinan, dan pemberdayaan masyarakat yang juga diharapkan dapat meningkatkan pertumbuhan perkapita. Tujuan penelitian ini untuk menganalisis pengaruh Produk Domestik Regional Bruto (PDRB), Indeks Pembangunan Manusia (IPM), Upah Minimum (UM) terhadap Penyerapan Tenaga Kerja (PTK). Populasi dalam penelitian ini adalah seluruh Sektor Industri di Provinsi Jawa Timur Tahun 2019 – 2023 yang terdiri dari 29 kabupaten dan 9 kota. Teknik pengambilan sampel yang digunakan dalam penelitian ini yaitu secara sampling jenuh yang menghasilkan seluruh Sektor Industri di Provinsi Jawa Timur Tahun 2019 – 2023 yang terdiri dari 29 kabupaten dan 9 kota. Teknik analisis yang digunakan adalah uji asumsi klasik, uji regresi linier berganda, dan uji hipotesis. Hasil penelitian secara parsial menyatakan bahwa Produk Domestik Regional Bruto (PDRB), Indeks Pembangunan Manusia (IPM), Upah Minimum (UM) berpengaruh terhadap Penyerapan Tenaga Kerja (PTK). Hasil penelitian secara simultan menyatakan bahwa Produk Domestik Regional Bruto (PDRB), Indeks Pembangunan Manusia (IPM), Upah Minimum (UM) berpengaruh terhadap Penyerapan Tenaga Kerja (PTK).